LAPORAN KASUS BERBASIS BUKTI: PENGARUH KOMPRES AIR HANGAT TERHADAP PENGURANGAN NYERI PERSALINAN KALA I FASE AKTIF - Lestari, Anastasya Deby; Wisnu Wardhani, Sri (Jurnal Kesehatan Siliwangi, 2024)
Labor pain is a common complaint experienced by women during childbirth, especially during the active phase of the first stage of labor. Previous research has shown that primiparous women tend to experience more intense pain compared to multiparous women. Objective: This study aims to evaluate the effectiveness of warm water compresses in reducing the intensity of labor pain during the active phase of the first stage of labor in women giving birth at UPTD Puskesmas Garuda. Methods: The study design used a case study of women in the active phase of the first stage of labor. The variables observed were the intensity of pain before and after the application of warm water compresses. Results: The results of the case study showed a significant decrease in pain intensity after the application of warm water compresses. Conclusion: Warm water compresses were proven to be effective in reducing the intensity of labor pain during the active phase of the first stage of labor in women giving birth at UPTD Puskesmas Garuda. Implications: These findings can be a clinical recommendation for healthcare workers, especially midwives, to use warm water compresses as one of the non-pharmacological methods for managing labor pain.